PENGARUH SKEPTISISME PROFESIONAL AUDITOR, ETIKA PROFESI, KOMITMEN PROFESIONAL AUDITOR, DAN KEAHLIAN AUDIT TERHADAP PEMBERIAN OPINI - Widiarini, Kadek Yulia; Suputra, I.D.G. Dharma (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
The purpose of this study is to demonstrate empirically the effect of the  auditor's professional skepticism, professional ethics, professional commitment auditors and audit expertise of the accuracy of giving opinions by the auditor at the Public Accounting office in Bali. This research was conducted at nine offices of public accounting firm in Bali in 2016 with auditors as many as 73 people from 81 sampled through the method of sample saturated. The data collection is done by distributing questionnaires and using multiple linear regression analysis. The results showed that: 1) professional skepticism auditor positive effect on the accuracy of giving opinions by the auditors, 2) professional ethics positive effect on the accuracy of giving opinions by the auditor, 3) professional commitment auditor positive effect on the accuracy of giving opinions by the auditor, and 4) audit expertise positive effect on the accuracy of the audit opinion by the auditor.
Keywords: Skepticism Auditor Professional, Professional Ethics, Professional Commitment Auditor, Audit Expertise, Accuracy Giving Opinion